Placental Related Disorders of Pregnancy - Mistry, Hiten D.; Lee, Eun (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue "Placental Related Disorders of Pregnancy" was edited by Dr Hiten D. Mistry, Department of Women and Children's Health, School of Life Course and Population Health Sciences, King's College London, London, UK and Dr Eun D. Lee, Department of Obstetrics and Gynecology, Virginia Commonwealth University Health System, Richmond, VA, USA.